Electronic Information Board Based on AVR Atmega128 for TEWS in Cilacap - Galih Mustiko Aji; Artdhita Fajar Pratiwi; Purwiyanto Purwiyanto; Chairunnisa Chairunnisa; Achmad Munir (Institute of Advanced Engineering and Science, 2018)
Dissemination methods of tsunami Information in Cilacap uses voice and siren. There are some constraints on the methods, especially in social aspects for particular society. Utilization of electronic information board is one of alternative solutions that can be offered to the society in responding tsunami information or warning. In this paper, a wireless electronic information board is designed to display the tsunami disaster warning visually. In normal condition or when there is no disaster, the information board can be utilized to display the information about evacuation procedure. The proposed electronic information board is implemented in multicolor using three sets of LED dot matrix panel P10 which have 32 x 16 pixels resolution and is controlled using microcontroller. The result showed that this device was capable to show the tsunami information such as “Status Awas”, “Status Siaga”, “Status Waspada”, and “Evacuation Route”.